Crystal structure analysis principles and practice. - Clegg, William, 1949-; Blake, Alexander J.; Cole, Jacquelyn M. (Oxford : Oxford University Press, 2009)
By choosing an approach that avoids undue emphasis on the mathematics involved, this book gives practical advice on topics such as growing crystals, solving and refining structures, and understanding and using the results.
Previous ed.: 2002.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crystals -- Structure